7.4k views
5 votes
-3х – 4y = 17 -6x - 4 y = 2

User Sorana
by
5.2k points

1 Answer

6 votes

Given


\begin{gathered} -3x-4y=17 \\ -6x-4y=2 \end{gathered}

Procedure


\begin{gathered} -3x-4y=17 \\ + \\ 6x+4y=-2 \\ \\ 6x-3x+4y-4y=17-2 \\ 3x=15 \\ x=(15)/(3) \\ x=5 \end{gathered}

Now, solving for y


\begin{gathered} 6x+4y=-2 \\ 4y=-2-6x \\ y=(-2-6x)/(4) \\ y=(-2-6\cdot5)/(4) \\ y=(-32)/(4) \\ y=-8 \end{gathered}

The answer would be x = 5 and y = -8

User Martin Vysny
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.